Analysis of acute COVID-19 including chronic morbidity: protocol for the deep phenotyping National Pandemic Cohort Network in Germany (NAPKON-HAP) - Steinbeis, Fridolin; Thibeault, Charlotte; Steinbrecher, Sarah; Ahlgrimm, Yvonne; Haack, Ira an; August, Dietrich Christian; Balzuweit, Beate; Bellinghausen, Carla; Berger, Sarah; Chaplinskaya-Sobol, Irina; Cornely, Oliver; Doeblin, Patrick; et al. (Infection, 2024)
The severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) pandemic causes a high burden of acute and long-term morbidity and mortality worldwide despite global efforts in containment, prophylaxis, and therapy. With unprecedented speed, the global scientific community has generated pivotal insights into the pathogen and the host response evoked by the infection. However, deeper characterization of the pathophysiology and pathology remains a high priority to reduce morbidity and mortality of coronavirus disease 2019 (COVID-19).